A Single‐Dot Perovskite Spectrometer (Adv. Mater. 33/2022). Issue 33 (18th August 2022) - Guo, Linqi; Sun, Haoxuan; Wang, Min; Wang, Meng; Min, Liangliang; Cao, Fengren; Tian, Wei; Li, Liang
Abstract : Microspectrometers In article number 2200221, Haoxuan Sun, Liang Li, and co‐workers demonstrate a new perovskite spectrometer design that is free from any optical or mechanical components and only requires one detection point. Such a spectrometer design breaks the long‐standing restriction of footprint‐resolution, and represents an advance for hyperspectral imaging.